Effect of Mixing Pumpkin Puree With Wheat Flour on Physical, Nutritional and Sensory Characteristics of Biscuit - Gurung, Bina; Ojha, Pravin; Subba, Dilip (Journal of Food Science and Technology Nepal, 2016)
Physical, nutritional and sensory quality characteristics of semi sweet type biscuit made by mixing wheat flour and pumpkin puree were studied. Wheat flour and pumpkin puree were mixed in the ratio of 100:0, 90:10, 80:20, 70:30 and 60:40. Diameter and thickness of biscuit decreased and bulk density increased as the amount of pumpkin increased. The nutritional quality of biscuit was positively influenced by the incorporation of pumpkin. Pumpkin increased protein, crude fibre, calcium, carotene and vitamin C of biscuit. The sensory quality of biscuit made from the mixed flour containing 70 parts of wheat flour and 30 parts of pumpkin puree was best. The biscuit made fromthe flour of this composition contained 2.53% moisture, 9.7% protein, 12% fat, 0.51% crude fiber, 0.81% total ash, 76.98% carbohydrate, 13.01 mg/100g carotene, 1.04 mg/100g Vitamin C, 1.88 mg/100g iron, 35.6 mg/100g calcium and energy value of 454.72 Kcal/100g dry matter.